2020
DOI: 10.1590/1806-9282.66.12.1685
|View full text |Cite
|
Sign up to set email alerts
|

Is ionizing radiation a risk factor for anxiety in employees?

Abstract: SUMMARY OBJECTIVE: Workers describe many physical and mental symptoms when working in radiation areas. This study aimed to assess these symptoms in radiation workers using the Beck Anxiety Inventory (BAI). METHODS: A total of 42 radiation workers (22 males and 20 females, mean age 34±7 years) and 47 control subjects (22 males and 27 females, mean age 31± 8 years) who work in non-radiation areas in the hospital were included in the study. All participants anonymously filled out the Beck Anxiety Inventory (BAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Radiation exposure-associated emotional disturbances are common and manifest as anxiety and depression, among other symptoms ( 44 , 45 ). Therefore, we examined emotion-related symptoms in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure-associated emotional disturbances are common and manifest as anxiety and depression, among other symptoms ( 44 , 45 ). Therefore, we examined emotion-related symptoms in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study by Asli Kurtar Mansiroglu et al 1 , in which they demonstrated that radiation is likely to be a risk factor for anxiety among hospital staff, although, in our opinion, the author should combine more clinical cases to confirm this view.…”
Section: Dear Editormentioning
confidence: 95%
“…
Dear Editor,We read with great interest the study by Asli Kurtar Mansiroglu et al 1 , in which they demonstrated that radiation is likely to be a risk factor for anxiety among hospital staff, although, in our opinion, the author should combine more clinical cases to confirm this view.First, although the two groups of research objects selected by the researchers come from the same working environment, there are still some differences, which will affect the accuracy of the research results; the author should choose a more similar working environment to reduce the interference of relevant influencing factors and research conclusions.Second, the author's conclusion is only to prove that radiation is one of the risk factors affecting employee anxiety. However, the further influencing mechanism is not determined.
…”
mentioning
confidence: 99%
“…Although ionizing radiation (IR) is known to be harmful, the use of radiation is increasing in many as of industry and medicine ( 1 3 ). Because IR-induced cellular damage comprises a very diverse and complex sequence of molecular events, it is very difficult to protect and prevent ( 4 ).…”
Section: Introductionmentioning
confidence: 99%